2019
DOI: 10.3390/ijms20071611
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MicroRNA in Lung Cancer

Abstract: Lung cancer is the most devastating malignancy in the world. Beyond genetic research, epigenomic studies—especially investigations of microRNAs—have grown rapidly in quantity and quality in the past decade. This has enriched our understanding about basic cancer biology and lit up the opportunities for potential therapeutic development. In this review, we summarize the involvement of microRNAs in lung cancer carcinogenesis and behavior, by illustrating the relationship to each cancer hallmark capability, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(192 citation statements)
references
References 178 publications
(156 reference statements)
2
189
1
Order By: Relevance
“…The X-chromosome contains an unusually high number of miRNAs, 118 compared to an average of 40-50 on the autosomes [148]. These miRNAs are regulators of a diverse array of processes, many of which are relevant to cancer [131,149,150].…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 99%
“…The X-chromosome contains an unusually high number of miRNAs, 118 compared to an average of 40-50 on the autosomes [148]. These miRNAs are regulators of a diverse array of processes, many of which are relevant to cancer [131,149,150].…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 99%
“…Importantly, aberrant expression of small noncoding RNAs, miRNAs have been reported in multiple cancers [15,16] and has also been shown to modulate EMT and drug chemoresistance [17][18][19]. For example, miR-34a has been shown to be downregulated in 5-fluorouracil (5-FU) resistant colorectal cancer, and its restoration caused regaining of 5-FU sensitivity via its direct target, lactate dehydrogenase A [20].…”
Section: Research Papermentioning
confidence: 99%
“…Chen et al indicated that miR-144 negatively controls TIGAR expression and induces apoptosis and autophagy in Lung Cancer [138]. MiR-144 is detected in lung cancer cells with the expression of upregulated glucose transporter 1 (GLUT1) and enhanced glucose uptake [139]. Moreover, miR144-5p increases the radiosensitivity in NSCLC cells by targeting activating transcription factor 2 (ATF2) [140].…”
Section: Mir-144 In Lung Cancermentioning
confidence: 99%